2018
DOI: 10.1128/mbio.00961-18
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa Complement of Lactate Dehydrogenases Enables Use of d - and l -Lactate and Metabolic Cross-Feeding

Abstract: Lactate is thought to serve as a carbon and energy source during chronic infections. Sites of bacterial colonization can contain two enantiomers of lactate: the l-form, generally produced by the host, and the d-form, which is usually produced by bacteria, including the pulmonary pathogen Pseudomonas aeruginosa. Here, we characterize P. aeruginosa’s set of four enzymes that it can use to interconvert pyruvate and lactate, the functions of which depend on the availability of oxygen and specific enantiomers of la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 49 publications
(73 reference statements)
4
40
0
Order By: Relevance
“…Strong interactions between P. aeruginosa and various Streptococci also have been reported (28), although the importance of metabolite cross-feeding in mediating these interactions remains incompletely understood (57). Finally, in the model Pseudomonas supplied small amounts of D-lactate for Prevotella and Staphylococcus consumption, a prediction consistent with an in vitro study showing P. aeruginosa anaerobic production of the LldA enzyme catalyzing D-lactate synthesis (58).…”
Section: Resultssupporting
confidence: 82%
“…Strong interactions between P. aeruginosa and various Streptococci also have been reported (28), although the importance of metabolite cross-feeding in mediating these interactions remains incompletely understood (57). Finally, in the model Pseudomonas supplied small amounts of D-lactate for Prevotella and Staphylococcus consumption, a prediction consistent with an in vitro study showing P. aeruginosa anaerobic production of the LldA enzyme catalyzing D-lactate synthesis (58).…”
Section: Resultssupporting
confidence: 82%
“…Although the mechanism by which L. lactis induced growth in this co‐culture setting is unclear, 1 possible explanation is related to L. lactis ’s (anaerobic bacteria) capability to convert glucose (sugar in the mucin) into lactate . The lactate produced fermentatively by L. lactis and mucin may serve as an electron donor for aerobic respiration of Pseudomonas and cause proliferation of certain strains …”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, they showed that in the absence of bicarbonate (with HEPES) the apical P. aeruginosa CFU increased significantly and even more in the presence of high glucose (15 mM), suggesting that CFRD and acidity contribute to worsen infections [63]. On the other hand, in addition to reduce the pH, the increased lactate may contribute to the development of infections by supplying a carbon source to bacteria [64]. Also, particularly in diabetic patients, the glucose metabolism in bacteria may be an additional source of lactate, contributing to a reduced pH environment and to the microfilm formation [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in addition to reduce the pH, the increased lactate may contribute to the development of infections by supplying a carbon source to bacteria [64]. Also, particularly in diabetic patients, the glucose metabolism in bacteria may be an additional source of lactate, contributing to a reduced pH environment and to the microfilm formation [64,65].…”
Section: Discussionmentioning
confidence: 99%